2022
DOI: 10.1177/23259671221079794
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Consecutive Clinical Outcomes After Transtibial Root Repair for Posterior Meniscal Root Tears: A Multicenter Study

Abstract: Background: Prospective evaluation of clinical outcomes after posterior meniscal root repair utilizing a transtibial pullout technique is limited, and factors that may contribute to outcomes are unclear. Hypothesis: It was hypothesized that there would be an overall significant improvement in outcomes after root repair and that differences in clinical outcomes would correlate with age, body mass index (BMI), sex, and meniscal extrusion. Study Design: Case-control study; Level of evidence, 3. Methods: Consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Such an injury can be caused by trauma or degeneration, particularly in middleaged patients during activities of daily living, such as walking or descending stairs, and can lead to abnormal knee kinematics, increased contact pressure and cartilage damage [3]. Transtibial pullout repair is the most common method for re-establishing adequate root fixation, as it can restore normal knee function and reduce the risk of degenerative changes in the knee joint [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Such an injury can be caused by trauma or degeneration, particularly in middleaged patients during activities of daily living, such as walking or descending stairs, and can lead to abnormal knee kinematics, increased contact pressure and cartilage damage [3]. Transtibial pullout repair is the most common method for re-establishing adequate root fixation, as it can restore normal knee function and reduce the risk of degenerative changes in the knee joint [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The MM posterior root (MMPR) plays a crucial role in maintaining the meniscus's normal function by controlling its movement. A tear in the MMPR (MMPRT) can cause abnormal loading and movement of the meniscus, leading to accelerated articular cartilage degeneration in the knee joint [1,2]. MMPRTs are a significant concern in orthopaedic practice as they are associated with a range of functional impairments and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with partial meniscectomy, there is more evidence indicating that various repair surgical strategies, not only restore hoop tension of the medial meniscus but also prevent the progression of knee degenerative [11, 16, 33]. Arthroscopic transtibial pullout is the most widely used surgical method and has been reported associated with satisfactory outcomes [18, 31], however, results of MRI or second‐look arthroscopy studies evaluating the repaired meniscus have shown higher rates of incomplete healing or increased medial meniscal extrusion (MME) [27].…”
Section: Introductionmentioning
confidence: 99%